An application of the theory of planned behaviour to understand compliance with daytime running headlights law among motorcycle riders. Issue 2 (2nd April 2020) - Payani, Sadegh; Law, Teik Hua
Abstract: Fatal motorcycle crashes are a persistent problem in Southeast Asia. In many respects, road safety experts have acknowledged conspicuity issue as one of the main causes of such accidents. To mitigate this deficiency, daytime running headlights (DRHs) law has been documented among the widely exercised countermeasures. The present study aimed to explore socio-psychological factors shaping intentions towards use of DRHs among Malaysian motorcyclists, because compliance level with this rule has remained constant since 1996 (80%). For this purpose, a model was constructed through the Theory of Planned Behaviour (TPB) to evaluate factors affecting motorcyclists' intentions towards compliance with DRHs law. A series of statistical analyses were performed to explain the effect of these factors and to predict degree of compliance with this rule. The model applied on a sample of university students (N = 398) demonstrated that the TPB components could significantly predict motorcycle riders' behaviours and degree of compliance with DRHs law. Moreover, it would be of assistance to policy-makers to recognize groups of motorcyclists more likely to cause an increase in traffic accidents. In general, regular educational campaigns were recommended to raise awareness regarding consequences of not using DRHs and also to nurture factors influencing motorcyclists' attitudes towards DRHs.